Research activities related to rational use of drugs by integral general physicians of Santiago de Cuba municipality - Leonardo Ramos Hernández; Frey Vega Veranes; Osmany Alonso Ayala; Armando Quintana Polanco; Iliana de la Caridad García Carrion (Universidad de Ciencias Médicas de La Habana, 2024)
Introduction: In the current context of the knowledge society, research occupies a primordial place as a fundamental way to inquiry and search for new knowledge. Objective: To characterize the research activities of Integral General Physicians related to the rational use of medicines in Santiago de Cuba municipality. Material and Methods: An investigation was carried out with a mixed approach (quantitative and qualitative) in the municipality of Santiago de Cuba during the period from January to July 2022. The population were the 796 integral general physician who were working in doctor's offices or in the emergency services of the 17 health care areas of Santiago de Cuba municipality, during the study period. A sample of 269 of these professionals who gave their consent to participate in the research (33.79 % of the population) was selected using the two-stage cluster probabilistic sampling method. The research activities of integral general physician in rational use of drugs was considered as variable, which was assessed in five indicators by means of a survey, an interview and a documentary review. Results: The methodological triangulation of the results showed that the variable studied had a low level of frequency of performance (index of 0.16), the same level reached by the five indicators analyzed. Conclusions: The low level of performance characterized the research activities of integral general physician related to the rational use of drugs in Santiago de Cuba municipality.